The effect of an aminoguanidine derivative on adjuvant arthritis in rats - V. S. Motov; V. V. Bykov; A. V. Bykova; A. I. Vengerovskii (Бюллетень сибирской медицины)
Aim. To study anti-inflammatory, analgesic, and possible ulcerogenic effects of a novel aminoguanidine derivative in adjuvant arthritis (a model of rheumatoid arthritis) in rats.Materials and methods. The experiments were carried out on 42 outbred male Sprague Dawley rats. After modeling arthritis (starting from day 7 after the administration of complete Freund’s adjuvant), intramuscular injections of the aminoguanidine derivative (code LIS-M) at a dose of 2.5, 5, and 10 mg / kg or the reference drug diclofenac at a dose of 4 mg / kg were performed once a day for 22 days. The volume of the inflamed limb was measured twice a week, pain threshold was measured every week. After finishing the administration of the compounds, the levels of interleukin (IL) 1, IL-6, and tumor necrosis factor-α (TNFα) were measured in rat plasma, the ankle joint was histologically studied, and the gastric mucosa was studied to detect damage, ulcers, and scarring.Results. The aminoguanidine derivative, an inhibitor of inducible nitric oxide synthase, was more effective at the dose of 10 mg / kg than diclofenac at the dose of 4 mg / kg. It had anti-inflammatory and analgesic effects in the joint affected by complete Freund’s adjuvant, promoted restoration of the histologic structure in the synovial membrane and articular cartilage, and reduced the plasma concentration of IL-1, IL-6, and TNFα by 1.4–1.5 times. The LIS-M compound did not damage the gastric mucosa in rats with adjuvant arthritis.Conclusion. The aminoguanidine derivative LIS-M exerts potent anti-inflammatory and analgesic effects in adjuvant arthritis in rats (a model of rheumatoid arthritis). LIS-M has no ulcerogenic effect on the gastric mucosa in rats.